Psychometric evaluation in a Brazilian context of three instruments proposed to investigate affective and cognitive aspects of eating - Martins, Bianca Gonzalez [UNESP]; Silva, Wanderson Roberto da [UNESP]; Marôco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Springer Nature, 2024)
This study aims to cross-culturally adapt the Dietary Goal-Desire Incongruence Scale (DG-DI), Motivation for Dietary Self-Control Scale (MDSC), and Satisfaction with Dietary Behavior Scale (SWDB) into Portuguese; to evaluate data validity and reliability; and to analyze the dietary desire-goal incongruence, motivation for dietary self-control, and satisfaction with dietary behavior among Brazilian adults. This is a cross-sectional study. Data were collected online from adults aged 18–35 years. The validity (content, internal structure, external measures, item response and consequential) and reliability of data were assessed. The scores of instruments were compared according to sample characteristics by Student’s t-test (α = 5%). 1,921 people participated (age = 24.9 years [standard deviation = 4.6]; 74.2% women). The validity and reliability of the DG-DI and SWDB have been attested as originally proposed. For MDSC one item was removed (“…doctor recommendations”). Women (t=-6.84─5.28), and those who consider their eating as regular/poor (t=-32.96─15.42) showed greater dietary incongruence, greater external motivation to eating control and lower satisfaction with eating (P < 0.001). The Portuguese versions of DG-DI, MDSC, and SWDB were established. Data were valid and reliable. Sample characteristics were associated with desire-goal incongruence, motivations to regulate eating, and satisfaction with eating, which are important in assessing people’s eating behavior.
Keywords: Cognition; Eating behavior; Emotions; Psychometrics; Young adult